Anni's India diary - Axworthy, Ann. (Whispering Coyote, 1992)
A ten-year-old's diary entries chronicle the magical sights and sounds she and her family encounter as they explore India.
"A Treld Bicknell book"--P. facing t.p.
5.1
3-6
3-6
School Library Journal
Book Links (A.L.A.)
Keywords: Diaries -- Fiction; Diaries -- Fiction; India -- Fiction; India -- Fiction